Postpartum corticosterone and fluoxetine shift the tryptophan-kynurenine pathway in dams. (August 2021) - Qiu, Wansu; Go, Kimberly A.; Lamers, Yvonne; Galea, Liisa A.M.
Abstract: Perinatal depression (PND) affects 15% of mothers. Selective serotonin reuptake inhibitors (SSRIs) are currently the first-line of treatment for PND but are not always efficacious. Previously, we found significant reductions in plasma tryptophan concentrations and higher hippocampal proinflammatory cytokine, IL-1β levels, due to maternal SSRI treatment. Both inflammation and tryptophan-kynurenine metabolic pathway (TKP) are associated with SSRI efficacy in individuals with major depressive disorder (MDD). TKP is divided into neuroprotective and neurotoxic pathways. Higher metabolite concentrations of the neurotoxic pathway are associated with depression onset and implicated in SSRI efficacy. Metabolites in TKP were investigated in a rodent model of de novo postpartum depression (PPD) given treatment with the SSRI, fluoxetine (FLX). Dams were administered corticosterone (CORT) (40 mg/kg, s.c.), and treated with the SSRI, fluoxetine (FLX) (10 mg/kg, s.c.), during the postpartum for 22 days after parturition. Plasma TKP metabolite concentrations were quantified on the last day of treatment. Maternal postpartum CORT increased neurotoxic metabolites and co-enzyme/cofactors in dams (3-hydroxykynurenine, 3-hydroxyanthranilic acid, vitamin B2, flavin adenine dinucleotide). The combination of both CORT and FLX shifted the neuroprotective-to-neurotoxic ratio towards neurotoxicity. Postpartum FLX decreased plasma xanthurenic acid concentrations. Together, our data indicate higher neurotoxic TKP expression due to maternal postpartum CORT treatment, similar to clinical presentation of MDD. Moreover, maternal FLX treatment showed limited efficacy to influence TKP metabolites, which may correspond to its limited efficacy to treat depressive-like endophenotypes in the postpartum. Overall suggesting changes in TKP may be used as a biomarker of de novo PPD and antidepressant efficacy and targeting this pathway may serve as a potential therapeutic target. Highlights: Tryptophan-kynurenine pathway (TKP) is altered by postpartum corticosterone (CORT). Postpartum CORT increased neurotoxic metabolites (3-HK, 3-HAA). Postpartum fluoxetine (FLX) increased xanthurenic acid concentrations. Postpartum CORT and FLX together shifted the TKP balance towards neurotoxicity.